2021
DOI: 10.1177/1468087421998631
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental validation of cavitating flow in a multi-hole diesel fuel injector

Abstract: This study assesses the predictive capability of the ZGB (Zwart-Gerber-Belamri) cavitation model with the RANS (Reynolds Averaged Navier-Stokes), the realizable k-epsilon turbulence model, and compressibility of gas/liquid models for cavitation simulation in a multi-hole fuel injector at different cavitation numbers (CN) for diesel and biodiesel fuels. The prediction results were assessed quantitatively by comparison of predicted velocity profiles with those of measured LDV (Laser Doppler Velocimetry) data. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Only one-sixth of the flow domain was numerically simulated, due to symmetrical nozzle geometry, so as to reduce computational effort, as shown in Figure 3a. Unstructured grids were used-the same as those of [13], as shown in Figure 3b,c-with tetrahedral cells and five layers of prism cells on the walls in order to accurately resolve near-wall turbulence. The maximum aspect ratio and skewness of all grids were 11.2 and 0.759, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one-sixth of the flow domain was numerically simulated, due to symmetrical nozzle geometry, so as to reduce computational effort, as shown in Figure 3a. Unstructured grids were used-the same as those of [13], as shown in Figure 3b,c-with tetrahedral cells and five layers of prism cells on the walls in order to accurately resolve near-wall turbulence. The maximum aspect ratio and skewness of all grids were 11.2 and 0.759, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…When the local pressure at the core of these vortices goes below the vapour pressure, the liquid starts to form cavitation pockets. As explained by Kumar et al [13], there are two types of such cavitating structures, which have been observed frequently in several experimental studies: The first type is hole-to-hole connecting vortex cavitation, which has been noted as an arc-shaped vortex, connecting two adjacent holes and the recess between the needle and the injector wall. The second observed type of these cavitation structures is a double counter-rotating vortical cavitation structure, originating from the needle wall and entering the opposing injector holes.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations